2020
DOI: 10.1111/ggi.14036
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of 90‐day mortality in older people with healthcare‐associated pneumonia

Abstract: Aim: The Quick Sequential Organ Failure Assessment, and confusion, urea, respiratory rate, blood pressure and age (CURB-65) scores have been used as prognostic factors of mortality related to healthcare-associated pneumonia. However, aspiration pneumonia remains unclear. Methods: A cross-sectional, prospective cohort study was carried out with 130 inpatients aged ≥75 years at a Geriatric ward of Kyorin University Hospital, Japan. We investigated the utility of aspiration pneumonia-related factors, latency of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In addition, unstable posture can be distracting and can interfere with chewing and bolus transfer. Next, if the participant sleeps while eating, a decreased level of consciousness may delay the swallowing reflex, which has previously been reported to be associated with aspiration and pneumonia 21,22 . Likewise, when the participant has difficulty concentrating on eating, inappropriate timing of swallow is considered to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, unstable posture can be distracting and can interfere with chewing and bolus transfer. Next, if the participant sleeps while eating, a decreased level of consciousness may delay the swallowing reflex, which has previously been reported to be associated with aspiration and pneumonia 21,22 . Likewise, when the participant has difficulty concentrating on eating, inappropriate timing of swallow is considered to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Next, if the participant sleeps while eating, a decreased level of consciousness may delay the swallowing reflex, which has previously been reported to be associated with aspiration and pneumonia. 21,22 Likewise, when the participant has difficulty concentrating on eating, inappropriate timing of swallow is considered to occur. It has also been suggested that frail older adults are less able to withstand the physical strain of eating and are more likely to experience fatigue and difficulty in stabilizing their posture while eating.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Atrial fibrillation : Studies have indicated that the detachment of mural thrombus resulting from atrial fibrillation was also a significant cause of AIS. Furthermore, a separate study involving 130 hospitalized patients aged over 75 with AP demonstrated that atrial fibrillation significantly reduced the 90-day survival rate of patients (P = 0.039) [ 33 ]. (5) There were also studies reporting that patients with poor organ function (such as Cardiac, Renal, and Hepatic insufficiency ) and overall nutritional status ( Prealbumin ) caused by long-term disease status might also have an increased susceptibility to AP [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the predictors, no variable selection was performed since the deletion of variables, even non-significant ones, could impair predictive accuracy [20]. Following a review of the existing studies, we established the final prediction models with 19 predictors associated with outcomes that had been used in previous studies [16,[21][22][23][24][25][26][27][28][29]. The following predictor data were collected at admission: patient age (65-69, 70-74, 75-79, 80-84, 85-89, 90-94, and �95 years), sex, BMI (<17.0, 17.0-18.4, 18.5-24.9, 25.0-29.90, and �30.0) [30], need for assistance with at least one of the ten activities of daily living (ADL) in the Barthel index (feeding, bathing, grooming, dressing, bowel control, bladder control, toilet use, transfers from bed to chair, mobility on level surfaces, and stairs) [31], malnutrition, consciousness level (using the Japan coma scale: 0: alert; 1-3: delirious; 10-30: somnolent; and 100-300: coma), emergency hospitalization, previous unplanned hospitalization for aspiration pneumonia within the last 90 days at the same hospital, and comorbidities.…”
Section: Predictorsmentioning
confidence: 99%